Enhancing the sensitization efficiency of erbium doped organic complexes by heavy halogen substitution. Issue 26 (21st June 2018) - Hu, J. X.; Karamshuk, S.; Gorbaciova, J.; Ye, H. Q.; Lu, H.; Zhang, Y. P.; Zheng, Y. X.; Liang, X.; Motevalli, M.; Abrahams, I.; Hernández, I.; Wyatt, P. B.; et al.
Abstract : Photosensitisation of IR luminescence from an organic erbium complex is much greater with Zn(Cl-FBTZ)2 than with Zn(FBTZ)2 . Abstract : Lanthanide complexes with organic ligands have been of interest due to the possibility of sensitising lanthanide ions through the antenna effect. We have recently shown that the zinc(ii ) salt of 2-(3, 4, 5, 6-tetrafluoro-2-hydroxyphenyl)-4, 5, 6, 7-tetrafluorobenzothiazole, Zn(FBTZ)2, can provide very high levels of sensitisation to organic erbium complexes whilst maintaining very high quantum yields for the erbium near-infra-red luminescence. We now report the spectroscopic properties of the zinc(ii ) salts of 2-(3, 4, 5, 6-tetrafluoro-2-hydroxyphenyl)-6-chloro-4, 5, 7-trifluorobenzothiazole and 2-(3, 4, 5, 6-tetrafluoro-2-hydroxyphenyl)-6-bromo-4, 5, 7-trifluorobenzothiazole. The substitution of a single chlorine atom into the chromophore is sufficient to double the sensitisation efficiency compared to the fully fluorinated chromophore. This result implies a 50% reduction in the pump intensity needed to achieve population inversion in the erbium ions.